A PENTALOGIA HOMOTEXTUAL EM MÁRCIO EL-JAICK - Estéfano Rogério Santana Oliveira (2024)
Literature is the artistic expression of human beings through writing. Among the possible themes that literature itself can present to contemporary society, homoeroticism has timidly presented some authors who have fictionalized this universe since centuries ago and found themselves on the fringes of the literary canon. Contemporary Brazilian literature is beginning a process of publicizing new homoerotic works, and authors who find hemselves in this so-called literary marginality are also seeking to have their texts ratified, thus expanding the field of studies on homoeroticism in national literature. However, this work was divided as follows: the first chapter presents the writer Márcio El-Jaick and his entire career as a writer; the second chapter deals with the approach to homoeroticism in literature and also with homotextuality; and the third chapter is the analysis of the five novels written, building his literary pentalogy. Rio de Janeiro-born author Márcio El-Jaick, a trained journalist with a literary award under his belt, began writing fiction in 1999, bringing a new way of reflecting on the behavior of homoerotic subjects and their experiences. Based on this concern, can the five works presented here be classified as homotexts? Although the author discusses the theme of male homoeroticism, this is still considered an inappropriate topic by some literary critics in academia. Therefore, we want to conform the five texts within the categories defended by the American theorist Jacob Stockinger, in his text homotextuality: a proportion, from 1978. Also, as each of the texts presented and analyzed within the literary pentalogy project, fit into the categories established by Stockinger, it is worth mentioning that this study project based on a pentalogy was already organized by Rodrigo Silva Cerqueira, in Literature as a project, in 2018. Finally, our objective is to bring together El-Jaick's pentalogy from the perspective of explanatory and bibliographical research, linking them to a single bias that is homoeroticism, with the purpose of opening the field of research for the constitution of a critical fortune and enabling future studies on the literary production of the writer Márcio El-Jaick.. Keywords: Contemporary Brazilian literature; Male homoeroticism; Homotextuality; Literary pentalogy; Márcio El-Jaick.